The Lateral Hypothalamus: An Uncharted Territory for Processing Peripheral Neurogenic Inflammation - Fakhoury, Marc; Salman, Israa; Najjar, Wassim; Merhej, George; Lawand, Nada (Frontiers in Neuroscience, 2020)
The roles of the hypothalamus and particularly the lateral hypothalamus (LH) in the regulation of inflammation and pain have been widely studied. The LH consists of a parasympathetic area that has connections with all the major parts of the brain. It controls the autonomic nervous system (ANS), regulates feeding behavior and wakeful cycles, and is a part of the reward system. In addition, it contains different types of neurons, most importantly the orexin neurons. These neurons, though few in number, perform critical functions such as inhibiting pain transmission and interfering with the reward system, feeding behavior and the hypothalamic pituitary axis (HPA). Recent evidence has identified a new role for orexin neurons in the modulation of pain transmission associated with several inflammatory diseases, including rheumatoid arthritis and ulcerative colitis. Here, we review recent findings on the various physiological functions of the LH with special emphasis on the orexin/receptor system and its role in mediating inflammatory pain.